Inhabiting territories at risk: Spatial appropriations and symbolic disputes in two peripheral neighborhoods of Quito - Alfredo Santillán; Elisa Puga-Cevallos (Íconos)
Through anthropology, the notion of culture has been introduced into the study of risks and natural disasters in order to understand the production of meaning, a contribution that goes beyond the positions of physical and probabilistic sciences. This article incorporates the notion of inhabiting to the debate, considering the modes and tensions of the daily reproduction of life in territories considered risky. Two neighborhoods are considered – which are similar in terms of context but have different qualities – through ethnographic methods that capture cognitive processes and strategies of adaptation and coexistence for guaranteeing material and symbolic permanence. This focus contributes to the debate on biases regarding risk management that, in practice, tend to abstract them from the space in which they are located and contributes to making explicit the divergences between the analyses of scientists, institutions, and populations. Through the observation of processes of domestication of space and the rationalities that underly them, the categorization of risk is debated as a mechanism for dealing with a context of economic dearth and absence of basic services. It is concluded that, for understanding the positions of people in relation to contingency or their proximity to a harm, one must consider their emotional attachments, their forms of inhabiting territory, and their perspectives of the future.